Signal processing of little elements monopulse direction finder in the conditions of strong interference using neural networks - S. V. Kozlov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The algorithm of direction finding of a useful signal source in a low-element monoimpulse direction finder with a quadrant antenna array based on a multilayer perceptron is considered. A distinctive feature of the algorithm is the use of modules and phases of elements of the normalized upper-triangular correlation matrix of processes at the outputs of the receiving channels as input information. The results of comparative analysis of the accuracy of direction finding of the useful signal achieved by using neural network and statistical algorithms of functioning are presented.